Thursday

November 27, 2014

November 27, 2014

Posted by **Karli** on Friday, January 29, 2010 at 4:33pm.

3y+5-2y+3=6y+5-6y

- Math -
**Ms. Sue**, Friday, January 29, 2010 at 4:43pm3y+5-2y+3=6y+5-6y

y + 8 = 5

y = -3

- Math -
**Karli**, Friday, January 29, 2010 at 4:44pmI don't get how you got the answer. What steps did you do?

- Math -
**Ms. Sue**, Friday, January 29, 2010 at 4:48pm3y+5-2y+3=6y+5-6y

First, combined like terms.

y + 8 = 5

Subtracted 8 from both sides of the equation.

y = -3

**Answer this Question**

**Related Questions**

Math - We have an important chemsitry test due and I want to make sure that I do...

English - 1. He can not solve the math problem. 2. He cannot solve the math ...

MATH PLEASEEEEE - I have a question, if f(x)=x/2 and g(x)=3x+1 find: a) (f+g)(x...

math - actually, in a addition to the question i posted a few minutes ago, can ...

Math - Solve by eliminnation methods 2x-4y=5 2x-4y=6 solve the system by ...

MATH PLEASE HELP! - Solve each system 3x+2y= -2 9x- y= -6 I know how to solve ...

Math - Solve for S: r^2s-5s=7. Solve for b: L= 4a^2b. I'm confused about how to ...

math - solve for the indicated variable: a. temperature formula solve for F: K=5...

math - Solve systems by substitution 5x - 2y = -5 y - 5x = 3 Substitute 5x + 3 ...

Math Analysis - 6. Prove that f(x) = (3/4)x^4 + 2 and g(x) = (4sqrt(108x-216))/3...